Progresses of Somatostatin Quantification for Clinical Practice - Yang, Wenjuan; Li, Jing; Gao, Jinhang; Huang, Zhiyin; Tang, Chengwei (Current Pharmaceutical Analysis, 2015)
Somatostatin (SST), a cyclic polypeptide, exerts a wide range of biological effects. As a result, decreased SST in plasma or tissues usually plays an important role in pathogenesis of various disorders. Exogenous supplement of SST or its analogues has been applied as an effective medical intervention in many diseases. The quantification of SST in plasma or tissues may provide a more rational application of SST in clinical practice. Currently, several methods for SST quantification have been established. The advantages and drawbacks of these methods are reviewed for clinical selection or further study. Moreover, necessary collection, extraction and preservation of samples for SST quantification are also recommended. Surface plasmon resonance (SPR) is a label-free optical detection technique for measuring biomolecular interactions in real-time. Among the several quantitative methods, an SPR-based immunoassay is suggested as a potential method for real-time SST quantification for clinical practice.
Keywords: somatostatin